Analisis Struktur Dan Aspek Kepribadian Dalam Novel Béntang Hariring Karya Dian Hendrayana: Kajian Psikologi Sastra - Ai Ageng Sari; Leni Nur'aeni (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
The purpose of this study is to describe the story stucture in the novel using Iskandarwassid’s theory and describe the personality aspects using Sigmund Freud’s theory. The method used in this study is the descriptive analysis method. Based on the results of the study, the theme in the novel Béntang Hariring by Dian Hendrayana contains the theme of struggle and a life full of simplicity, the plot used in this novel is a mixed plot (Forward plot and backward plot), the characters in this novel consist of 1 Main Character, 1 Second Character and 8 additional characters, the setting in this novel consist of 9 Time Settings, 12 Place Setting and Atmosphere Settings and Social Setitngs in this novel are the environment where people socialize and moral messages. The personality aspects of the characters in this novel are the main character, Nia, whose most dominant personality is the Ego aspect. The second character, Nia’s mother, whose most dominant personality is Id and Ego. Additional characters, Salma, Wina, Mrs. Yanti, have the same personality, whose most dominant personality is the Id aspect. Additional characters, Pa Yana, Pa Hendra and principal whose most dominant personality is the Ego aspect.